Estabilidade de agregados em resposta à aplicação de biochars em solos de pastagens degradadas do sul do Estado Espírito Santo. - Santos, Danilo Andrade (2014)
Partially charred organic materials, most commonly known as biochars, has attracted theattention of Soil Science to understanding its effects on soil properties. This study aimed to evaluate the effects of adding biochars eucalyptus, sugar cane bagasse an